2015
DOI: 10.1371/journal.pone.0127489
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section Frequency among Immigrants, Second- and Third-Generation Women, and Non-Immigrants: Prospective Study in Berlin/Germany

Abstract: ObjectiveThe frequency of caesarean section delivery varies between countries and social groups. Among other factors, it is determined by the quality of obstetrics care. Rates of elective (planned) and emergency (in-labor) caesareans may also vary between immigrants (first generation), their offspring (second- and third-generation women), and non-immigrants because of access and language barriers. Other important points to be considered are whether caesarean section indications and the neonatal outcomes differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
1
12
2
3
Order By: Relevance
“…We found no differences in emergency caesarean section rates across groups of women with and without migration background in the BaBi birth cohort study. This is in line with the Berlin perinatal study [15,20]. It is important to note, though, that the BaBi participants with a migration background do not necessarily represent the diversity of migration biographies in Germany.…”
Section: Implications Of the Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We found no differences in emergency caesarean section rates across groups of women with and without migration background in the BaBi birth cohort study. This is in line with the Berlin perinatal study [15,20]. It is important to note, though, that the BaBi participants with a migration background do not necessarily represent the diversity of migration biographies in Germany.…”
Section: Implications Of the Resultssupporting
confidence: 82%
“…Although Germany is a diverse country and one of the main reception countries for migrants in Europe, there has been little systematic investigation regarding differences in emergency caesarean section rates by migration status and socioeconomic status. In a recent prospective study conducted in Berlin, emergency caesarean section rates did not differ depending on migration status and level of education [15]. Income, however, was not included in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We observed no differences in terms of labour induction or caesarean section rates between RIs and LTRs, whereas inconsistent results have been published by other authors, some reporting higher and others reporting lower rates of caesarean sections in RI populations 22 23 29 30. A certain number of obstetrical complications such as failure to progress labour, inflammatory syndrome during labour, fetal distress and severe perineal lacerations were more prevalent among RIs.…”
Section: Discussioncontrasting
confidence: 74%
“…For instance, one study showed a lower probability of utilization especially among 1st generation migrants (odds ratio (OR): 0.58; confidence interval (CI): 0.40–0.83) [ 23 ]. Inpatient care was assessed by the number of hospitalizations and elective surgeries (mostly caesarean section) [ 17 , 18 , 23 , 25 , 26 , 29 , 30 , 37 39 ]. The 10 studies revealed an inconsistent pattern in terms of ethnical disparities.…”
Section: Resultsmentioning
confidence: 99%